Risk of Transmission of Antimicrobial Resistant Escherichia coli from Commercial Broiler and Free-Range Retail Chicken in India - Hussain, Arif; Shaik, Sabiha; Ranjan, Amit; Nandanwar, Nishant; Tiwari, Sumeet K.; Majid, Mohammad; Baddam, Ramani; Qureshi, Insaf A.; Semmler, Torsten; Wieler, Lothar H.; Islam, Mohammad A.; Chakravortty, Dipshikha; et al. (Frontiers in Microbiology, 2017)
Multidrug-resistant Escherichia coli infections are a growing public health concern. This study analyzed the possibility of contamination of commercial poultry meat (broiler and free-range) with pathogenic and or multi-resistant E. coli in retail chain poultry meat markets in India. We analyzed 168 E. coli isolates from broiler and free-range retail poultry (meat/ceca) sampled over a wide geographical area, for their antimicrobial sensitivity, phylogenetic groupings, virulence determinants, extended-spectrum-β-lactamase (ESBL) genotypes, fingerprinting by Enterobacterial Repetitive Intergenic Consensus (ERIC) PCR and genetic relatedness to human pathogenic E. coli using whole genome sequencing (WGS). The prevalence rates of ESBL producing E. coli among broiler chicken were: meat 46%; ceca 40%. Whereas, those for free range chicken were: meat 15%; ceca 30%. E. coli from broiler and free-range chicken exhibited varied prevalence rates for multi-drug resistance (meat 68%; ceca 64% and meat 8%; ceca 26%, respectively) and extraintestinal pathogenic E. coli (ExPEC) contamination (5 and 0%, respectively). WGS analysis confirmed two globally emergent human pathogenic lineages of E. coli, namely the ST131 (H30-Rx subclone) and ST117 among our poultry E. coli isolates. These results suggest that commercial poultry meat is not only an indirect public health risk by being a possible carrier of non-pathogenic multi-drug resistant (MDR)-E. coli, but could as well be the carrier of human E. coli pathotypes. Further, the free-range chicken appears to carry low risk of contamination with antimicrobial resistant and extraintestinal pathogenic E. coli (ExPEC). Overall, these observations reinforce the understanding that poultry meat in the retail chain could possibly be contaminated by MDR and/or pathogenic E. coli.